Governance Zakat Produktif: Membangun Lembaga yang Transparan dan Akuntabel - Rufaedah, Dina Anisya; Patih, Husnama (Program Studi Ekonomi Syariah STAI Senori Tuban, 2024)
Productive zakat is a Sharia economic instrument that has great potential to empower the people's economy. However, successful implementation is highly dependent on governance (governance) the good one. This research aims to examine the importance of building a transparent and accountable zakat management institution in supporting the success of productive zakat. Through a literature review and case analysis, this research concludes that transparency and accountability are the main keys in building public trust in institutions. Transparency includes disclosure of information regarding the management of zakat funds, distribution mechanisms, and the results achieved. Meanwhile, accountability means that the institution is accountable to all stakeholders, including muzakki, mustahik, and the government. This research also identifies several factors that can support the realization of a transparent and accountable zakat management institution, such as the existence of a good financial management system, independent monitoring mechanisms, and active community participation in the decision-making process.